Association between CYP3A5 genotypes with hypertension in Chinese Han population: A case-control study. (3rd April 2017) - Li, Zhanzhan; Chen, Peng; Zhou, Tao; Chen, Xiaofang; Chen, Lizhang
ABSTRACT: Background : The association of CYP3A5 gene polymorphisms with hypertension in the Chinese population is unknown. We explored the association between the CYP3A5 (rs776746) gene and hypertension in the Chinese Han population. Methods : Using a case-control design, 340 cases and 254 controls were enrolled from the Third Affiliated Hospital of South Medical University between July and December of 2015. We used a standardized questionnaire to collect data regarding age, sex, smoking, drinking, family history of hypertension, and physical exercise. Height and weight were measured, and the body mass index (BMI) was calculated by weight/height 2 . Blood pressure was measured three times after 5 min of rest with at least 15 s between measurements, and the mean was considered the final BP. A Clinical examination was conducted. Results : A total of 594 participants, including 340 cases and 254 controls, were entered into the analyses. The genotype frequencies of the CYP3A5 G>A polymorphism did not deviate from the Hardy-Weinberg equilibrium. The genotype frequencies among the cases were 38.8% (GA, 132 individuals), 42.9% (GG, 146 individuals), and 18.2% (AA, 62 individuals). The differences in genotype between the cases and the controls were statistically significant. The AA genotype was associated with an elevated risk of hypertension after adjusting for potential confounders in Model 2. There was no interaction between smoking and the CYP3A5 genotype, while the interaction between drinking and the CYP3A5 genotype was significant. Conclusion : The CYP3A5 gene may be associated with the risk of hypertension in the Chinese Han population, and this effect may be exacerbated by drinking.